2013
DOI: 10.1017/s0033291713002092
|View full text |Cite
|
Sign up to set email alerts
|

Netmums: a phase II randomized controlled trial of a guided Internet behavioural activation treatment for postpartum depression

Abstract: BackgroundDespite the high prevalence of postnatal depression (PND), few women seek help. Internet interventions may overcome many of the barriers to PND treatment use. We report a phase II evaluation of a 12-session, modular, guided Internet behavioural activation (BA) treatment modified to address postnatal-specific concerns [Netmums Helping With Depression (NetmumsHWD)].MethodTo assess feasibility, we measured recruitment and attrition to the trial and examined telephone session support and treatment adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
271
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(281 citation statements)
references
References 49 publications
7
271
1
2
Order By: Relevance
“…Supported online psychological interventions can improve clinical outcomes in mothers with postnatal depression (Kaplan, Solomon, Salzer, & Brusilovskiy, 2014; O'Mahen et al., 2014) and parenting in parents with and without mental health problems (Love et al., 2016; Sanders, Baker, & Turner, 2012; Sanders, Dittman, Farruggia, & Keown, 2014). Additionally, three studies of online Triple P indicated child behaviour improvements (Love et al., 2016; Sanders et al., 2012; Sanders, Dittman et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Supported online psychological interventions can improve clinical outcomes in mothers with postnatal depression (Kaplan, Solomon, Salzer, & Brusilovskiy, 2014; O'Mahen et al., 2014) and parenting in parents with and without mental health problems (Love et al., 2016; Sanders, Baker, & Turner, 2012; Sanders, Dittman, Farruggia, & Keown, 2014). Additionally, three studies of online Triple P indicated child behaviour improvements (Love et al., 2016; Sanders et al., 2012; Sanders, Dittman et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…22 Cognitive behavioral therapy (CBT) for AD has been associated with better infant orientation, engagement and emotional regulation in women with improvement in their depression symptoms. 23 CBT has been studied more extensively for postpartum depression, 21 and computer-based interventions for postpartum depression that involved personal coach calls 24 or weekly phone call support 25 significantly improved symptoms. Modified CBT for women with AD has been attempted in two pilot studies.…”
mentioning
confidence: 99%
“…ICBT with clinician guidance has been found to be effective for depression and other common mental disorders (e.g., Andersson, Cuijpers, Carlbring, Riper & Hedman, 2014;Cuijpers, Donker, van Straten & Andersson, 2010;Kuester, Niemeyer & Knaevelsrud, 2016: O'Mahen et al, 2014, insomnia (Trockel, Karlin, Taylor & Manber, 2014) as well as a range of somatic conditions (e.g., Andersson, 2016;Cuijpers et al, 2010;Cuijpers, van Straten & Andersson, 2008). In one of the more recent reviews, the overall treatment effect for ICBT for depression, based on 32 trials and 5642 patients, was estimated to g = 0.67 (Andrews et al, 2018).…”
Section: Clinical Effect and Attritionmentioning
confidence: 99%